Risk Appetite and Decision Making in Venezuelan Companies - Doria, Domingo (2014)
The following investigation aims to determine the risk dispositions and decision making considerations of individuals in Venezuelan companies. Even though the main topics have been widely covered in numerous experiments and studies, the specifications in literature of risk appetite and decision making in the Bolivarian Republic Venezuela is almost non-existent. Both topics are considered to be crucial for the wellbeing of individuals and nations, having a direct impact on wealth. Accordingly, risk appetite and decision making dispositions in this study were analysed by implementing a set of games and a survey to a group of participants from a Venezuelan company. According to the results, the subjects of the study displayed risk adverse attitudes, as they aimed to preserve their wealth and achieve agreements with their counterparts to distribute economic resources. Furthermore, elements such as wage of the financial status of their opponents and the socio-economic situation of Venezuela were found to be significant determinants to their decisions